Impact of Microclimate and Indoor Plants on Air Ion Concentration (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Saturation of air ions is essentially important for all living beings, especially for human health. Existing sanitary norms provide that concentration of small ions has to be in range of 400-50000 ions cm-3 and unipolarity coefficient 0.4 ≤ K ≤ 1.0. Many species of indoor plants emit organic volatile compounds and air ions, therefore they could be used for improving the quality of indoor air. The results show that ionization level of indoor air is significantly insufficient and selected species of indoor plants are not able to improve it. They serve rather as supplementary surfaces for ion absorption. Possible interaction between microclimate, ion concentration and indoor plants in different times of the day is analyzed.